Understanding Orang Asli Participation in Sport: Some Methodological Issues - Rahim, Baidruel Hairiel Abd; Diah, Nurazzura Mohamad (School of Social Sciences, USM, 2017)
Social science disciplines like anthropology, sociology, political sciences, economics, education and so on often work with vulnerable groups in an attempt to understand their live experiences. Qualitative methodology and ethnography in particular helps a researcher to identify the behavior that contradicts beliefs, opinions and emotions from the participant perspectives. In the West, the use of ethnography to study sport and vulnerable group is significant considering the rich amount of information potentially obtained during fieldwork. This paper aims to elucidate some methodological issues related to the study of sport particularly among Orang Asli (aborigine) athletes. To obtain relevant data, in-depth interview, focus group interview (FGI) and participant-observation were conducted among ten Orang Asli athletes from the Jakun tribe in Pekan, Pahang. These athletes whose age are between 14 and 17 years old have participated in various sports like track and field and cross country running. The findings discovered that vignettes are useful to help participants express themselves and disclose their experiences in sports. Vignettes have been utilized efficiently in all FGI sessions as interaction stimulants between participants and researchers. Interestingly, the low-context communication between the researchers and Orang Asli athletes at the beginning of most interviews have transformed into a high-context communication. It is also suggested that researchers role as a teacher, coach and sportsman have helped them in managing the relationships in the field. In conclusion, employing qualitative methodology to study vulnerable group requires careful selection of methods and consideration of the approach needed.